VIOLATION OF THE IMMUNE STATUS AND ITS CORRECTIONIN PATIENTS WITH CHRONIC CHOLECYSTITIS (CAHIERS MAGELLANES-NS, 2024)
Chronic cholecystitis – is the most common pathology of the hepatobiliary system, occurring with a frequency of more than 10%, has no tendency to decrease. Immune processes play a role in the development and maintenance of the inflammatory process in the gallbladder. Moreover, in patients with chronic cholecystitis, a secondary immunodeficiency state develops. The development of an immunocorrective method of treatment in these patients is an urgent task in modern gastroenterology. The aim of the work was to study the parameters of the immune system and conduct an immunocorrective method of treatment in patients with chronic cholecystitis. Material and methods. We conducted a prospective study of the parameters of the immune system in 48 patients with chronic cholecystitis and in 36 healthy individuals. Lymphocyte immunophenotyping was used using the indirect immunofluorescence method. The concentration of serum immunoglobulins (Ig) A, M, and G was determined by radial immunodiffusion, and the level of circulating immune complexes was determined by the precipitation method. The results of studies on the study of the immune status in patients with CC showed the presence of an imbalance in the functioning of the immune system. At CC, a 0.6–fold decrease in the relative value of the total pool of T(CD3)–lymphocytes compared with the control (p<0.001) was revealed, and this was typical for both Groups. At the same time, the 2nd degree of disorders according to A.M. Zemskov was observed (–0.43 and –0.41 in groups 1 and 2, respectively). The results obtained indicate a significant and significant – 0.6–fold – decrease in blood in patients with CC fraction of Ts(CD8) (p<0.001), 0.8–fold decrease in the level of Th(CD4) (p <0.001) and inversion of IRI, expressed in its significant increase. The relative value of B(CD19)–lymphocytes was statistically higher than the values of the Control Group (p<0.01). Their production increased by 1.3 and 1.5 times in Groups 1 and 2, respectively, compared with the Control Group. Traditional methods of treatment did not lead to the restoration of impaired immune status in patients with chronic cholecystitis. The use of Thymoptinum as a corrector of immune system disorders in these patients contributed to the effective elimination of disorders of the cellular immunity. The introduction of timoptin into the combined treatment regimen in patients of the 2nd Group led to an increase in both cellular and humoral immunity. A statistically significant increase in the total pool of T–lymphocytes (CD3 phenotype), B (CD19)–lymphocytes (p<0.001), as well as a decrease in IRI with an increase in the proportion of Ts (CD8) was registered, which, of course, is a predictor of the effectiveness of immunocorrective therapy for CC, since this led to a decrease in the intensity of autoimmune processes. At the same time, in Group 2 Ki for T(CD3)–cells was 78.4%, and for B–lymphocytes (CD19) – 28.8%, which undoubtedly reflects the positive dynamics of changes from the immunocorrection performed. IgM and IgA levels remained low compared to the Control Group. The use of Thymoptinum as a corrector of immune system disorders in patients with CC contributed to the effective elimination of disorders of the cellular link of immunity – T (CD3)–lymphocytes and its subpopulations, as evidenced by the Ki coefficients. At the same time, a decrease in the tension of the humoral component of the immune system was also revealed. Thymoptinum had a therapeutic and immunomodulatory effect in patients with CC.